Evaluating Post-Interventional Occlusion Grades of Cerebral Aneurysms with Transcranial Contrast-Enhanced Ultrasound (CEUS) Using a Matrix Probe - Wendl, C. M.; Eiglsperger, J.; Schuierer, G.; Jung, E. M. (Ultraschall in der Medizin - European Journal of Ultrasound, 2015)
Purpose: The main goal of cerebral endovascular aneurysm therapy is the complete occlusion of the aneurysm. Along with the development of new aneurysm treatment devices, repeated controls are necessary. We examined whether contrast-enhanced ultrasound can help to monitor aneurysms after endovascular treatment.Materials and Methods: We prospectively examined 12 patients after coiling (7 patients) or flow diverter (FD) implantation (5 patients). These patients were examined with transcranial contrast-enhanced ultrasound using a matrix probe (1 – 5 MHz). Doppler sonography, Power Doppler, contrast harmonic imaging (CHI) and Power Doppler sonography (CPD) were included in the examination. Digital subtraction angiography with 3 D reconstructions served as the gold standard. Two radiologists decided in consensus about the degree of aneurysm occlusion separately in CEUS and digital subtraction angiography using a 4-point grading scheme.Results: The degree of occlusion of the 12 aneurysms comparing the two imaging modalities was identical in 10 cases. In two cases CHI and CPD showed a small aneurysm remnant after coiling in the center of the coil pack while in digital subtraction angiography the aneurysms seemed completely occluded.Conclusion: The investigation indicates that contrast-enhanced ultrasound is a supportive, noninvasive method for post-interventional controls of intracranial aneurysms due to its ability to display not only macro- but also microvascularization.
Keywords: contrast-enhanced ultrasound; aneurysm; flow diverter; contrast harmonic imaging